Identificación de la garrapata en bovinos (Bos Taurus) del Cantón Quijos, Parroquia San Francisco de Borja. - Villamarín Álvarez., Kimberley Katiuska (2022)
The objective of this research was to determine the species of ticks in cattle (Bos Taurus) of the Quijos Canton, San Francisco de Borja Parish, sampling 150 female Holstein cattle from 5 neighborhoods (Campo Libre, La Florida, Santa Teresita and El Paraíso). ), the samples were collected from October 4 to November 7, 2021, 300 specimens were obtained, through a thorough examination of the entire body surface of the animals in a systematic manner in the pre-established anatomical regions: head, neck, hindquarters, anterior train, belly, udder, tail, perineum and vulva of each animal, later they were stored in sterile bottles with 70% ethanol, each sample taken was properly labeled, which were grouped in number of 5 for their physical similarity, and observed the stereomicroscope and with the guide of pictorial and dichotomous keys, the presence of two genera of ticks Rhipicephalus (B) microplus with 96% and Ixodes spp c was established. With 4%, the genus Riphicephalus microplus was identified according to male and female due to two very striking and important aspects, the female does not maintain a marked dorsal shield on its entire surface while the male does, the caudal process is very visible in the male and in the female it is incipient or small; the ticks were located in all the anatomical zones analyzed, of which the head and neck were the ones with the highest concentration with 23.15 and 22.74 units, respectively; the Santa Teresita and El Paraíso neighborhoods of the San Francisco de Borja parish, showed the presence of ticks per animal of 154 and 157 respectively, interpreted as a high degree of infestation.